PENGEMBANGAN MEDIA PEMBELAJARAN TRUTH OR DARE PADA MATERI CERITA FIKSI KELAS IV SEKOLAH DASAR - Tyas, Hesty Dwy Wahyuning; Abdul Aziz Hunaifi; Aprilia Dwi Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Learning media functions as an intermediary or channel or bridge in communication activities (delivery and reception of messages) between communicators (message transmitters or teachers) and communicants (message recipients or students). The aim of this research is develop Truth or Dare card learning media and determine the feasibility and response of students to the learning media developed for learning Indonesian with Fiction Story material in class IV SDN 3 Tiron. This research uses the Research and Development (R&D) development method with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation), with the research subjects being fourth grade students at SDN 3 Tiron. The data collection instruments used were interviews, validation sheets, and student response questionnaires. The validation results obtained from material experts were 94% in the